Comparative Effects of Blended Herbal Extracts and Mixed Prebiotics on Growth Performance, Carcass Yields and Intestinal Morphology of Broiler Chickens - Karukarach, Tasama; Rakangthong, Choawit; Bunchasak, Chaiyapoom; Poeikhampha , Theerawit (International Journal of Poultry Science, 2016)
An experiment was conducted to determine the effect of blended herbal extracts (BHEs; Origanum vulgare L., Cinnamomum zeylanicum Nees. and Capsicum frutescens L.) and mixed prebiotics (MPs; Mannanoligosaccharide and beta-glucan) in feed on the growth performance, carcass yield and intestinal morphology of broilers. Two hundred and seventy male broiler chickens (Arbor Acres) were divided into 3 groups and each group consisted of 5 replicates of 18 chicks each. The experiment was established as a completely randomized design. There were 3 experimental diets: 1) a control diet; 2) the control diet supplemented with blended herbal extracts (BHEs; 150 g/t); and 3) the control diet supplemented with mixed prebiotics (MPs; 2,000 g/t). At age 35 days, the results indicated that the feed conversion ratio (FCR) was significantly improved by supplementation with BHEs compared to MPs (P